Colaizzi's Methods in Descriptive Phenomenology: Basis of A Filipino Novice Researcher - Gumarang Jr., Bernardo K.; Mallannao , Romel C.; Gumarang , Brigitte K. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Descriptive phenomenology is a common methodology employed in social science research to investigate and describe people's lived experiences. It is both a philosophy and a scientific technique, and it has undergone several modifications as it expanded from the original European movement to encompass the American movement. This paper discussed and explained the process in applying Colaizzi’s method in descriptive phenomenological research under the field of education. This paper used a published research study, which the process of Colaizzi was utilized to give enough help in sorting, organizing, analyzing and presenting the narrative dataset. The main objective of using Colaizzi's descriptive phenomenology method was to generate an exhaustive description of the phenomena addressing the challenges of student moms in the midst of pandemic. Descriptive phenomenology is particularly beneficial for correctly describing the problems of student moms, and the result may be applied as the voice of this group of students during pandemic. This can be a basis of School Institutions in crafting policies as well the National Government.